20 Neural plasticity for functional rehabilitation after stroke. Issue 8 (13th July 2017) - Ward, Nick
Abstract : Nick Ward is Reader in Clinical Neurology and Honorary Consultant Neurologist – Sobell Department of Motor Neuroscience, UCL Institute of Neurology and National Hospital for Neurology and Neurosurgery. He is clinical lead of the first dedicated Upper Limb Neurorehabilitation Programme at The National Hospital for Neurology and Neurosurgery, Queen Square. In his research, he uses structural and functional brain imaging to study how reorganisation of brain networks supports recovery of upper limb movement after stroke. He is Associate Editor of the Journal of Neurology, Neurosurgery and Psychiatry, and Neurorehabilitation and Neural Repair. He is co-editor of the Oxford Textbook of Neurorehabilitation. Stroke is the commonest cause of severe physical disability in the world. Inability to use the arm and hand is a major contributor to this problem. Currently, recovery of arm/hand movement is unpredictable and it is not clear why some stroke survivors recover whilst others do not. After stroke, there is little restoration of neural tissue, and so reorganisation of surviving neural networks appears to be important for recovery of function. Optimal recovery of movement therefore depends on at least two things. Firstly, preservation of neural pathways that convey sensory signals into the brain and instructions to move out of it. Secondly, a post-stroke increase in the potential for neuroplasticity that allows surviving brain regions to reorganise into effective networks capable of supporting arm and hand function. Failure of either will lead to failure of recovery. Advances in brain imaging will soon allow us to examine changes in organisation of the human brain after stroke at multiple levels, ranging from large scale networks to alterations in synaptic physiology. These techniques will provide the appropriate intermediate level of description with which to bridge the gap between what we know about recovery after stroke from animal models compared to what we know from studies of behaviour in humans. A more detailed knowledge of how these processes are related to impairment and recovery following stroke will provide a mechanistic framework for understanding how to treat our patients more effectively. References: . Rondina JM, Filippone M, Girolami M, Ward NS. Decoding post-stroke motor function from structural brain imaging. NeuroImage: Clinical2016Aug 2;12:372– 80 . Ward NS. Restoring brain function after stroke – bridging the gap between animals and humans. Nat Rev Neurol2017 (in press).